A new species of Pseudatrichia Osten Sacken (Diptera: Scenopinidae) from North America - Winterton, Shaun L. (Zootaxa, 2009)
A new species of the North American genus Pseudatrichia Osten Sacken is described. Pseudatrichia bezarki sp. nov. is described based on a male and female reared from wood-boring beetle galleries in Pinus sp. from Arizona (United States).